Equine CD4(+) CD25(high) T cells exhibit regulatory activity by close contact and cytokine-dependent mechanisms in vitro - Hamza, Eman (Blackwell Science Inc, 2011)
Horses are particularly prone to allergic and autoimmune diseases, but little information about equine regulatory T cells (Treg) is currently available. The aim of this study therefore was to investigate the existence of CD4(+) Treg cells in horses, determine their suppressive function as well as their mechanism of action. Freshly isolated peripheral blood mononuclear cells (PBMC) from healthy horses were examined for CD4, CD25 and forkhead box P3 (FoxP3) expression. We show that equine FoxP3 is expressed constitutively by a population of CD4(+) CD25(+) T cells, mainly in the CD4(+) CD25(high) subpopulation. Proliferation of CD4(+) CD25(−) sorted cells stimulated with irradiated allogenic PBMC was significantly suppressed in co-culture with CD4(+) CD25(high) sorted cells in a dose-dependent manner. The mechanism of suppression by the CD4(+) CD25(high) cell population is mediated by close contact as well as interleukin (IL)-10 and transforming growth factor-β1 (TGF-β1) and probably other factors. In addition, we studied the in vitro induction of CD4(+) Treg and their characteristics compared to those of freshly isolated CD4(+) Treg cells. Upon stimulation with a combination of concanavalin A, TGF-β1 and IL-2, CD4(+) CD25(+) T cells which express FoxP3 and have suppressive capability were induced from CD4(+) CD25(−) cells. The induced CD4(+) CD25(high) express higher levels of IL-10 and TGF-β1 mRNA compared to the freshly isolated ones. Thus, in horses as in man, the circulating CD4(+) CD25(high) subpopulation contains natural Treg cells and functional Treg can be induced in vitro upon appropriate stimulation. Our study provides the first evidence of the regulatory function of CD4(+) CD25(+) cells in horses and offers insights into ex vivo manipulation of Treg cells.